Exploring opportunities for providing pharmacists with feedback on their practice and performance around the electronic Minor Ailments Service in Scotland. (14th January 2014) - Paudyal, Vibhu; Hansford, Denise; Cunningham, Scott; Stewart, Derek
Abstract Background The electronic Minor Ailments Service (e‐MAS), implemented in all community pharmacies in Scotland since 2006, allows pharmacists to manage minor ailments at no charge to patients including provision of medication, advice or referral. E‐MAS is supported through an electronic network, 'E‐pharmacy', which is managed by National Health Service Scotland. E‐pharmacy has the capacity to remotely record e‐MAS activities, such as details of medicines supply and patient registration allowing provision of feedback to community pharmacies. Objective The aim of this research was to explore community pharmacists' views on potential utility of e‐MAS performance data as a source of feedback on the quality of their own practice. Method Focus groups and telephone interviews with community pharmacists from four geographical Health Board areas in Scotland were utilised. Key findings Twenty community pharmacists took part in the study. Pharmacists highlighted potential for feedback to support practice in areas related to medicines supply (for example, formulary adherence and reimbursements to pharmacies from the Health Boards), patient registration and the impact of the new guidelines on their practice. Participants deemed individualised feedback to be potentially more useful than local or national aggregated data sets. Issues of confidentiality and participants' disinterest in feedback were potential barriers to the use of the data. Conclusions This qualitative study has identified potential benefits of performance feedback data to pharmacists' practice. Key barriers to the use of the feedback, such as the issues of privacy and confidentiality need to be addressed by National Health Service information providers. Findings warrant further large scale evaluation of their application to practice.